2008
DOI: 10.1086/587473
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Planes and the BarlessMBH‐σ Relation for Supermassive Black Holes

Abstract: The residuals about the standard M bh -relation correlate with the effective radius, absolute magnitude, and Sérsic index of the host bulge, giving rise to an apparent black hole ''fundamental plane.'' However, we show that the elliptical galaxies do not define such a plane. Instead, it is a handful of barred galaxies, which are shown to systematically deviate from the M bh -relation by log M bh % À0:5 to À1.0 dex (their -values are too large) and generate much of the aforementioned three-parameter correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
185
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(216 citation statements)
references
References 109 publications
(108 reference statements)
24
185
6
1
Order By: Relevance
“…The evidence of a correlation between the residuals and the effective radius is obtained by considering only spiral and lenticular bulges. Graham (2008b) reached the same result studying a sample of 40 galaxies. In particular he found that the barred galaxies are responsible for much of the trend between the M • − σ residuals and R e , whereas the elliptical galaxies alone do not provide substantial support for the existence of a FP plane for SMBHs.…”
Section: A Possible Fundamental Plane For Supermasssive Black Holessupporting
confidence: 62%
See 1 more Smart Citation
“…The evidence of a correlation between the residuals and the effective radius is obtained by considering only spiral and lenticular bulges. Graham (2008b) reached the same result studying a sample of 40 galaxies. In particular he found that the barred galaxies are responsible for much of the trend between the M • − σ residuals and R e , whereas the elliptical galaxies alone do not provide substantial support for the existence of a FP plane for SMBHs.…”
Section: A Possible Fundamental Plane For Supermasssive Black Holessupporting
confidence: 62%
“…Plotting the dependence of the residual of the M • −σ relation on R e and M , the results of Hopkins et al (2007b) are clearly in conflict with that of the other authors (Aller & Richstone 2007;Graham 2008b;Sani et al 2011). Of course, the explanation of this difference has to be found in the different analysis approach.…”
Section: A Possible Fundamental Plane For Supermasssive Black Holesmentioning
confidence: 77%
“…Different observations now question that BH-host correlations indeed appear as tight as previously claimed for all types of galaxies (e.g., Hu 2008;Graham 2008;Gültekin et al 2009;Graham & Li 2009). Significant outliers exist (e.g., Mathur et al 2001;Grupe & Mathur 2004;Watson et al 2007), BHs are currently observed also in the centres of bulgeless galaxies (e.g., Ghosh et al 2008;Satyapal et al 2009;Araya salvo et al 2012), and the AGN-starformation correlations disappear for all but highest luminosity AGNs (Shao et al 2010;Grier et al 2011).…”
Section: Introductionmentioning
confidence: 74%
“…For example, the two most commonly used proxies, stellar velocity dispersion and bulge luminosity, lead to rather different estimates of φ(M bh ) (e.g., Lauer et al 2007a;Tundo et al 2007, but see also Graham 2008): the luminosity-based estimate predicts many more massive black holes. To date, there is no consensus on which is correct, at least for the more massive galaxies.…”
Section: Introductionmentioning
confidence: 99%